2020
DOI: 10.1002/cam4.3230
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal microRNA‐4661‐5p–based serum panel as a potential diagnostic biomarker for early‐stage hepatocellular carcinoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 38 publications
0
35
0
Order By: Relevance
“…In particular, exo-miR-10b-5p appeared as a promising biomarker for early-stage HCC with an AUROC of 0.93, a sensitivity of 90.7% and specificity of 75.0% [ 35 ]. Another set of miRNAs, exo-miR-25-3p, exo-miR-1269a, exo-miR-4661-5p, and exo-miR-4746-5p with increased expression in HCC were found by selecting driver oncogenic miRNAs using analysis of miRNAs expression profiles from three different RNA sequencing datasets of human HCC [ 36 ]. In particular, serum exo-miR-4661-5p could detect HCC at all stages with AUROC of 0.92; even at early-stage HCC, the AUROC remained at 0.92.…”
Section: Microrna Biomarkersmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, exo-miR-10b-5p appeared as a promising biomarker for early-stage HCC with an AUROC of 0.93, a sensitivity of 90.7% and specificity of 75.0% [ 35 ]. Another set of miRNAs, exo-miR-25-3p, exo-miR-1269a, exo-miR-4661-5p, and exo-miR-4746-5p with increased expression in HCC were found by selecting driver oncogenic miRNAs using analysis of miRNAs expression profiles from three different RNA sequencing datasets of human HCC [ 36 ]. In particular, serum exo-miR-4661-5p could detect HCC at all stages with AUROC of 0.92; even at early-stage HCC, the AUROC remained at 0.92.…”
Section: Microrna Biomarkersmentioning
confidence: 99%
“…Also, Table 1 , which summarizes a series of microRNAs that are not further discussed in the review, clearly shows that most studies that evaluate circulating miRNAs as potential biomarkers for HCC detection were conducted using Asian cohorts, which are generally characterized by a high-frequency of HBV-induced HCC, and no or small numbers of HCC induced by HCV, alcohol or NAFLD. In addition, these studies were conducted involving small groups of patients and have yet to be validated within large cohort of patients [ 35 , 36 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Microrna Biomarkersmentioning
confidence: 99%
“…Moreover, aberrantly regulated exo-miRs can promote HCC progression and metastasis by altering the genetic network [ 20 ]. An in vitro study by Lin et al, exosome-mediated miR delivery was shown to promote the EMT and metastasis in HCC [ 21 ]. However, few studies have investigated circulating exo-miR profiles as metastasis predictors or promoters in HCC.…”
Section: Discussionmentioning
confidence: 99%
“…For the early detection of HCC, serum exo-miR-10b-5p has been reported to be a promising biomarker, with 90.7% sensitivity and 75.0% specificity at the cut-off value of 1.8-fold[ 40 ]. Notably, a novel panel comprising exo-miR-4661-5p and exomiR-4746-5p yielded a best fit AUC of 0.947 with a sensitivity of 75% and a specificity of 91.7% for early-stage HCC[ 41 ]. A separate study reported that the combination of exo-miR-122, exo-miR-148a, and AFP was able to distinguish early HCC from cirrhosis with an AUC of 0.931[ 42 ].…”
Section: Non-invasive Biomarkers For Early Diagnosis Of Hccmentioning
confidence: 99%